EARLY ALLOGRAFT DYSFUNCTION AND ACUTE KIDNEY INJURY AFTER LIVER TRANSPLANTATION: DEFINITIONS, RISK FACTORS AND CLINICAL SIGNIFICANCE - L. Y. Moysyuk; V. N. Poptsov; Y. G. Moysyuk (Вестник трансплантологии и искусственных органов)
This review discusses issues related to intensive care in recipients of transplanted liver in the early postoperative period, with an emphasis on contemporary conditions and attitudes that are specific for this group of patients. Early allograft dysfunction (EAD) requires immediate diagnosis and appropriate treatment in case. The causes of the EAD and therapeutic tactics are discussed. Acute kidney injury (AKI) and renal failure are common in patients after transplantation. We consider etiology, risk factors, diagnosis and treatment guidelines for AKI. The negative impact of EAD and AKI on the grafts survival and recipients is demonstrated.